Effects of chloride concentration on CO2 corrosion of novel 3Cr2Al steel in simulated oil and gas well environments. Issue 2 (13th September 2018) - Tan, Chengtong; Xu, Xiuqing; Xu, Lining; Yin, Chengxian; Qiao, Lijie
Abstract : The corrosion behavior of novel 3Cr2Al steel in simulated oil and gas well environments was investigated using scanning electron microscopy, electron diffraction spectroscopy, potentiodynamic polarization, and potentiostatic polarization. The results revealed that the corrosion rate of 3Cr2Al steel increased as the Cl − concentration increased. The thickness of the corrosion product film decreased as the Cl − concentration increased. The increase in Cl − concentration caused a decrease in pH value, subsequently causing an increase in the solubility of Cr(OH)3 and Al(OH)3 and hindering the deposition of corrosion product, eventually yielding a thinner corrosion film. Abstract : The corrosion behavior of novel 3Cr2Al steel in simulated oil and gas well environments was investigated using SEM, EDS, and polarization. The results revealed that the corrosion rate of 3Cr2Al steel increased as the Cl concentration increased. The thickness of the corrosion product film decreased as the Cl − concentration increased. The increase in Cl − concentration caused a decrease in pH value.